(untitled) (International Research in Economics and Finance, 2018)
Curtis Jr (2018) describes the objective of the university course, to convey intermediate and advanced concepts of theory of the firm to students using explanatory, graphical and mathematical methods of analysis. The only prerequisite for this course is successful completion of Calculus, Principles of Microeconomics, or equivalent. After completing the requirements in this course, students should have a sufficient set of skills to thoroughly analyze interesting economic questions and to effectively participate in (i) advanced undergraduate economics courses, (ii) core graduate economic theory courses, and (iii) graduate courses in the school of business, including MBA programs. The emphasis of this paper is that economics is the study of the efficient choices made by individuals, including consumers, workers, owners of firms and social planners Policy writers. Students and wealthy philanthropists reading this paper might conclude that corporate board members, and higher education endowment strategists and budget executives, should focus on and enhance the effectiveness of the individual, conditional on the capacity and constraints, whether they are innate, financial or political. Curtis Jr (2018) presents the teaching materials separately, attached to this document, presented in Microsoft Powerpoint slides, created by James Edward Curtis Jr (2001) and Microsoft Publisher slides, created by James Edward Curtis Jr (2014), for projector transparency presentation by university instructors, and created by James Edward Curtis Jr, for higher education student studies. Reviewers include Dr. John C Ham, Ph.D. from Princeton University, Tenured Professor and Provost, and Former Advisor.